Plasma Free Fatty Acids Metabolic Profile Among Uyghurs and Kazaks With or Without Type 2 Diabetes Based on GC-MS - Ma, Xiao-li; Meng, Lei; Li, Lin-lin; Ma, Li-na; Mao, Xin-min (Experimental and Clinical Endocrinology & Diabetes, 2018)
Free fatty acids (FFAs) participate in a variety of physiological functions. FFAs are associated with the development of type 2 diabetes mellitus (T2DM). Uyghurs and Kazaks have a different prevalence of T2DM, which cannot be explained by traditional risk factors. This study aimed to examine FFAs as potential biomarkers to distinguish between healthy and T2DM Uyghurs and Kazaks. This was a prospective study conducted at the Xianjiang Medical University from 01/2007 to 06/2010 in Uyghurs and Kazaks. The subjects were grouped as T2DM patients (Uyghurs: n=39; Kazaks, n=21) and controls (Uyghurs: n=35; Kazaks, n=40). Gas chromatography-mass spectrometry (GC-MS) and partial least squares discriminant analysis (PLS-DA) models were used to study the FFA profiles between Uyghurs and Kazaks with T2DM. PLS-DA analysis showed that among Kazaks, T2DM patients had lower C22:6, C18:3 n-6, and C20:3 n-6, but higher C22:0 levels compared with controls. Among Uyghurs, the most important variables to discriminate T2DM patients from controls were higher C22:6 and C20:4 n-6, and lower C22:0, C14:1, C18:3 n6, and C20:3 n6. Kazaks and Uyghurs displayed different FFA profiles between patients with T2DM and controls. These results suggest different risk factors and pathogenesis of T2DM between Kazaks and Uyghurs.
Keywords: free fatty acids; GC-MS; type 2 diabetes mellitus; Kazaks; Uyghurs